2014
DOI: 10.1007/s00520-014-2519-2
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of short- and long-term survival for advanced cancer patients after ICU admission

Abstract: Clinical factors associated with acute, critical status upon ICU admission, such as APACHE II score and need of CRRT, were associated with a higher risk of ICU mortality and short-term mortality than factors directly associated with the patient's cancer. To understand the relationship between ICU admission and long-term survival, however, we have to apply more comprehensive approach that also considers tumor characteristics and disease control status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 37 publications
3
12
0
Order By: Relevance
“…Third, the proportion of patients admitted with each cancer type reflects the range of tertiary services based at our hospital and the data may not be generalisable to general ICUs in hospitals without a tertiary cancer service. Fourth, patients admitted to our ICU were less sick with lower APACHE II and SOFA Scores on day of admission compared to other similar studies in the literature, 28 29 43 48 which may reflect differences in admission policy and bed availability. The Guy's Hospital site has no separate high-dependency unit, and 37.3% of patients in our study did not require organ support at time of admission, rather they were admitted for enhanced monitoring.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Third, the proportion of patients admitted with each cancer type reflects the range of tertiary services based at our hospital and the data may not be generalisable to general ICUs in hospitals without a tertiary cancer service. Fourth, patients admitted to our ICU were less sick with lower APACHE II and SOFA Scores on day of admission compared to other similar studies in the literature, 28 29 43 48 which may reflect differences in admission policy and bed availability. The Guy's Hospital site has no separate high-dependency unit, and 37.3% of patients in our study did not require organ support at time of admission, rather they were admitted for enhanced monitoring.…”
Section: Discussionmentioning
confidence: 56%
“…Most studies have demonstrated an association between short-term mortality and severity of acute illness, 27–30 greater number of failed organ systems 31–37 and increased requirement for organ support including mechanical ventilation, 23 30 38–40 vasopressors 36 38 39 41 and RRT. 29 42 Our analysis showed that APACHE II Score on admission to ICU was independently associated with worse hospital and 180-day mortality. Although a greater number of failed organ systems and the need for organ support at ICU admission were associated with worse hospital mortality in univariate analysis, only the need for RRT remained an independent risk factor for 180-day mortality.…”
Section: Discussionmentioning
confidence: 74%
“…A number of patients treated in an ICU have a difficult time returning to their lives after hospitalization and the health of some patients continued to decline following discharge [4][5][6]. The studies on long-term outcomes of ICU survivors are rare in Korea [7,8]. The long-term outcomes are much more difficult to follow-up and certain predictors for mortality after ICU discharge (e.g., quality of life and psychological problems) are not easily measurable.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that the prognostic factors important for the general population requiring PMV cannot be directly applied to cancer patients requiring PMV. In cancer patients requiring mechanical ventilation, several studies have shown that cancer status is an independent risk factor for increased mortality 79, 24 . We further found that weaning outcome was significantly related to long-term survival in cancer patients requiring PMV, even in patients with an uncontrolled cancer status.…”
Section: Discussionmentioning
confidence: 99%